Stability and global attractivity for a class of nonlinear delay difference equations - Binxiang Dai; Na Zhang (Discrete Dynamics in Nature and Society)
A class of nonlinear delay difference equations are considered and some sufficient conditions for global attractivity of solutions of the equation are obtained. It is shown that the stability properties, both local and global, of the equilibrium of the delay equation can be derived from those of an associated nondelay equation.